Mending: opportunities for Springville, Utah to counteract suburban sprawl - Weber, Michael Stewart (Kansas State University, 2010)
A 2009 survey conducted by the Pew Research Center for Social & Demographic Trends found that people living in suburban areas are significantly more satisfied with their communities than are residents of cities, small towns, or rural areas. With almost 50 percent of Americans living in suburban areas, and not enough infill opportunities to accommodate future population growth, suburban development will likely continue to be a primary location for development (Berens 2010). As suburbia continues to develop there are two options: continue to use conventional suburban strategies or implement alternative suburban strategies. The city of Springville, Utah is currently experiencing suburban growth near a future transit station to the west of the downtown core. Since suburban sprawl has already begun in this area, the city has an opportunity to design for growth and become a positive example of suburban development in the region. What are the possibilities and impacts of using conventional suburban strategies versus alternative suburban methods? A 60-acre tract of land in west Springville, Utah is planned and designed for development. The first master plan is designed to demonstrate Conventional Suburban Development. The second plan is designed to demonstrate Alternative Suburban Development. A comparative analysis of the two master plans accompanies the designs to compare the two solutions. This method has been used by New Urbanists to illustrate the difference in their method of suburban development. This tract includes a future transit station, a major highway corridor, and nearby access to Interstate 15. Additionally, the tract is located approximately two miles from downtown Springville. The focus of this study is to provide the background and evidence that there are design alternatives which can contribute to the mending of suburban sprawl. In this project, city officials, planners, developers, business owners, and housing consumers are provided with an objective comparative analysis of conventional versus alternative methods of suburban development in the Wasatch Front Region of Utah. The analysis of the two design proposals provides valuable insight into the feasibility or desirability of key design principles contained in each design proposal. The study provides compelling evidence that alternative methods of community design and suburban development are to be considered to help the region achieve its long range planning goals set forth in the Envision Utah initiative.
Keywords: Suburbia; Design guidelines; Suburban sprawl; Alternative suburban development; Sustainable; Envision Utah; Landscape Architecture (0390)